Differences in mortality and morbidity according to gestational ages and birth weights in infants with trisomy 18. (26th August 2015) - Imai, Ken; Uchiyama, Atsushi; Okamura, Tomoka; Ago, Mako; Suenaga, Hideyo; Sugita, Eri; Ono, Hideko; Shuri, Kyoko; Masumoto, Kenichi; Totsu, Satsuki; Nakanishi, Hidehiko; Kusuda, Satoshi
<x xml:space="preserve">Abstract</x> The aim of this study was to clarify the effects of gestational age and birth weight on outcomes of the infants. Medical records of 36 infants with trisomy 18 admitted to Tokyo Women's Medical University Hospital from 1991 to 2012 were reviewed retrospectively. We compared clinical characteristics between term infants (n = 15) and preterm infants (n = 21). There were one very‐low‐birth‐weight (VLBW) term infant (5%) and 12 VLBW preterm infants (80%). Although there were no significant differences in clinical characteristics and provided management between the two groups, none of the preterm infants achieved survival to discharge. On the other hand, 6 of 21 term infants (29%) achieved survival to discharge (P < 0.05). Similar results were obtained for comparisons between the VLBW infants and non‐VLBW infants. Multiple logistic regression analysis revealed that shorter gestational age had a more negative impact than lower birth weight to survival to discharge in infants with trisomy 18. In both preterm and term groups, the infants who died before 30 days commonly died of respiratory failure or apnea. Whereas, the infants who survived more than 30 days mostly died of heart failure. © 2015 The Authors. American Journal of Medical Genetics Part A Published by Wiley Periodicals, Inc.